2022
DOI: 10.3390/su14137538
|View full text |Cite
|
Sign up to set email alerts
|

PERMA Model of Well-Being Applied to Portuguese Senior Tourists: A Confirmatory Factor Analysis

Abstract: Tourism has been affirmed as an activity that promotes health and well-being. The present study aims to present a confirmatory analysis of the PERMA model in a sample of Portuguese senior tourists who visited the island of São Miguel (Azores). After approval of the study by the ethics committee (reference 6/2022), a Sociodemographic Questionnaire, PERMA Profiler, and Life Satisfaction Scale—SWLS were applied to 1083 senior tourists (≥55 years) of various nationalities. To evaluate the PERMA model for senior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Huber et al (2018) indicates that the behavior of German senior tourists changes with age. This factor also differentiated the way that PERMA elements were perceived by the Portuguese in tourism as indicated in the research conducted by Mendes et al (2022). Those authors observed no significant differences in the results of their studies conducted among men and women.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Huber et al (2018) indicates that the behavior of German senior tourists changes with age. This factor also differentiated the way that PERMA elements were perceived by the Portuguese in tourism as indicated in the research conducted by Mendes et al (2022). Those authors observed no significant differences in the results of their studies conducted among men and women.…”
Section: Discussionmentioning
confidence: 80%
“…As maximizing motivation and identifying opportunities are essential in identifying and guiding behavior (Loureiro et al, 2022), research efforts must combine motivation, lifestyle, life satisfaction, and demographic indicators, such as gender and level of education (Faranda & Schmidt, 2000;Quan et al, 2022;Streimikiene et al, 2021). A broad range of analysis is proposed by Mendes et al (2022). In their study, they described the relationship between the well-being of senior tourists and the following five measurable elements: Positive Emotion, Engagement, Relationships, Meaning, and Accomplishment (PERMA).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation